(untitled) (Scottish Historical and Archaeological Internet Reports, 2023)
A three-year community archaeology project was completed on behalf of the Hume Castle Preservation Trust at the village of Hume in the Scottish Borders. The project engaged with over 300 members of the public, providing training and volunteering opportunities in a suite of archaeological skills. The project work focused on Hume Village and its surrounding landscape; in particular Hume Castle and the remains of the former medieval village immediately surrounding it, and the associated kirkyard which housed the former Hume Parish Church. Extensive survey work was completed in the kirkyard and adjacent Glebe, in the grounds of Hume Castle, and at the castle itself. Excavations were completed in the castle grounds, the Glebe, and in the garden of West End Cottage in Hume Village. The results of the survey and excavation works portray the changing settlement pattern and use of land in the village area, particularly highlighting occupation and use of the former buildings surrounding the castle up to 200 years after its destruction. A similar pattern was found in the kirkyard, with continual use of the cemetery over 300 years after the abandonment, and probable destruction, of the former kirk. The results indicate that despite the destruction of its castle and kirk, the village of Hume has persevered, maintaining an important sense of place and memory in the landscape.